Water security, adaptation and gender:: the case of rainwater harvesting in Brazilian Semiarid - Nogueira, Daniela (Sustainability in Debate, 2017)
This article brings a reflexion on One Million Cisterns Programme’s contribution as a strategy to reduce drought impact on Brazilian Semiarid poorest population. It’s based on a case study supported by semi-structured interviews accomplished in Pernambuco and Paraíba rural communities. When analyzing gender mainstreaming impact in the programme, as well as rainwater harvesting systems in families daily life, it is observed that gendered water policies result in better conditions of health income and education, also enhancing capacity to cope and reducing population vulnerability.